PENGARUH JUMLAH KOLONI BAKTERI PLAK SUBGINGIVA TERHADAP JUMLAH TOTAL LEUKOSIT SELAMA KEHAMILAN - Praharani, Depi (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Gingivitis can occur during pregnancy. It is caused by subgingival plaque bacterial. They can enhance because level of estrogen and progesterone are elevated during pregnancy. At patient gingivitis showed that total count of leucocyte is bigger than patients with normal periodontal tissues. The objective of this study was to investigate the influence of the number of subgingival plaque bacterial colonies to total count of leucocyte in blood periphery. Subgingival plaque samples were collected from buccal surface of maxillary first molar. Hereinafter blood taken away from vein periphery and counted by total count leucocyte. The obtained data were analyzed with linear regression test. Statistical analysis showed that the influence of the number of subgingival plaque bacterial colonies to total count of leucocyte in blood periphery was found to be significant (P<0.05). The conclusion is that the number of subgingival plaque bacterial colonies can increase total count of leucocyte in blood periphery.